Metagenomics reveals contrasted responses of microbial communities to wheat straw amendment in cropland and grassland soils - Domitille Jarrige; Vincent Tardy; Valentin Loux; Olivier Rué; Abad Chabbi; Sébastien Terrat; Pierre-Alain Maron (Scientific Reports)
Abstract Soil microbial communities respond quickly to natural and/or anthropic-induced changes in environmental conditions. Metagenomics allows studying taxa that are often overlooked in microbiota studies, such as protists or viruses. Here, we employed metagenomics to characterise microbial successions after wheat straw input in a 4-month in-situ field study. We compared microbial successions patterns with those obtained by high throughput amplicon sequencing on the same soil samples to validate metagenomics as a tool for the fine analysis of microbial population dynamics in situ. Taxonomic patterns were concordant between the two methodologies but metagenomics allowed studying all the microbial groups simultaneously. Notably, our results evidenced that each domain displayed a specific dynamic pattern after wheat straw amendment. For instance, viral sequences multiplied in the early phase of straw decomposition, in parallel to copiotrophic bacteria, suggesting a “kill-the-winner” pattern that, to our knowledge, had not been observed before in soil. Altogether, our results highlighted that both inter and intra-domain trophic interactions were impacted by wheat amendment and these patterns depended on the land use history. Our study highlights that top-down regulation by microbial predators or viruses might play a key role in soil microbiota dynamics and structure.